Health state utilities associated with weight loss in type 2 diabetes and obesity. (31st December 2022) - Boye, Kristina S.; Matza, Louis S.; Stewart, Katie D.; Andrews, Haylee; Howell, Timothy A.; Stefanski, Adam; Malley, Karen G.; Ishak, K. Jack; Fernández Landó, Laura
Abstract: Introduction: Health state utilities associated with weight change are needed as inputs for cost-utility analyses (CUAs) examining the value of treatments for obesity and type 2 diabetes (T2D). Although some pharmaceutical treatments currently in development are associated with substantial weight loss, little is known about the utility impact of weight decreases greater than 10%. The purpose of this study was to estimate utilities associated with body weight decreases up to 20% based on preferences of individuals with obesity, with and without T2D. Methods: Health state vignettes were developed to represent respondents' own current weight and weight decreases of 2.5, 5, 10, 15, and 20%. Health state utilities were elicited in time trade-off interviews in two UK locations (Edinburgh and London) with a sample of participants with obesity, with and without T2D. Mean utility increases associated with each amount of weight decrease were calculated. Regression analyses were performed to derive a method for estimating utility change associated with weight decreases. Results: Analyses were conducted with data from 405 individuals with obesity (202 with T2D, 203 without T2D). Utility increases associated with various levels of weight decrease ranged from 0.011 to 0.060 in the subgroup with T2D and 0.015 to 0.077 in the subgroup without T2D. All regression models found that the percentage of weight decrease was a highly significant predictor of change in utility ( p  < .0001). The relationship between weight change and utility change did not appear to be linear. Equations are recommended for estimating utility change based on the natural logarithm of percentage of weight decrease. Discussion: Results of this study may be used to provide inputs for CUAs examining and comparing the value of treatments that are associated with substantial amounts of weight loss in patients with obesity, with or without T2D.